Effect of polymerized sewage on viscosity of polymer solution and countermeasures. (October 2019) - Dong, W T; Wang, K L; Qiu, Y; Peng, W
Abstract: In order to better analyze the influence of sewage on the viscosity of polymer solution, this paper uses BROOKFIELD viscometer to determine the viscosity value of solution. The results show that the viscosity decreases rapidly with the increase of the of polymer solution concentration of metal cations. Especially, the concentration of Mg 2+ and Ca 2+ have a great influence on the viscosity and the small increase of the concentration of Mg 2+ and Ca 2+ can lead to the decrease of the viscosity of HPAM solution. Na2 CO4 was chosen as the complexing agent to improve the viscosity of HPAM solution, and the viscosity increasing rate of HPAM solution with the concentration of 1500 mg/L reached 33.2%.